2014
DOI: 10.15580/gjea.2014.2.062614283
|View full text |Cite
|
Sign up to set email alerts
|

VAR Analysis of Economic Growth, Domestic Investment, Foreign Direct Investment, Domestic Savings and Trade in Rwanda

Abstract: This paper analyses real Gross Domestic Product (GDP), Domestic Investment (DI), Foreign Direct Investment (FDI), Domestic Savings (DS) and Trade (TR) in Rwanda for the period 1970 to 2011. GDP and DI have an upward trend and annual growth of real GDP was around 8% in average for all period. FDI and DS have remained below 2% of GDP each and trade balance of Rwanda is always negative. Augmented Dickey-Fuller (ADF) tests show that GDP, DI and FDI are not stationary at the level but the first differences are stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…A higher savings rate has been considered to be a major determinant of economic growth and development. Ruranga, Ocaya, and Kaberuka (2014) found that for the case of Rwanda "there is unidirectional causality from domestic savings to real gross domestic product". Relationship between savings and growth is not only direct but also may be looked at indirectly through other economic indicators, for instance investment.…”
Section: Introductionmentioning
confidence: 99%
“…A higher savings rate has been considered to be a major determinant of economic growth and development. Ruranga, Ocaya, and Kaberuka (2014) found that for the case of Rwanda "there is unidirectional causality from domestic savings to real gross domestic product". Relationship between savings and growth is not only direct but also may be looked at indirectly through other economic indicators, for instance investment.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies find opposite results, showing that FDI tends to have nonsignificant (or even negative) effects on economic growth in host countries [40][41][42][43][44][45], implying that FDI has negative effects on economic development or that the relationship between FDI and economic growth is positive but the effects are weak.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Economic growth is fundamental to the development of every society in the world. Foreign direct investment (FDI), in addition to other factors such as exports, exchange rate, domestic savings, and trade, contributes to economic growth and development [3].…”
Section: Introductionmentioning
confidence: 99%